How Companies Value Stock Prices After Going Public: Evidence from Emerging Pakistan economy - Muhammad Aamir; Hafiz Muhammad Nadeem; Khawer Naheed; Allah Bakhsh Khan (Journal of Accounting and Finance in Emerging Economies, 2018)
The purpose of this study is to estimate the accuracy and authenticity of valuation methods used by underwriters to set preliminary offer price. This study uses complete universe of all newly listed companies during 2000 to 2015 on Pakistan Stock Exchange. We analyzed the determinants of the Initial Public Offering (IPOs) by comparing the ex-ante and ex-post characteristics of IPOs firms. Binary logistic model was used for evaluation of variables. Results revealed that underwriters use four different valuation methods to set IPO preliminary offer price namely as dividend discount model (DDM), discounted cash flow method (DCF), peer groups multiple (MULT) and economic valuation method (EVA). This study used Binary Logistic Regression model to estimate the accuracy and authenticity of these valuation methods. Results of this study can help the portfolio managers for constructing their effective portfolio strategies. This study also helps to highly levered firms to get cheaper long term capital by going public. This study is also important for underwriters to counter check their valuation patterns for IPO firms.